2013
DOI: 10.1371/journal.pone.0081361
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of Olfactory Sensitivity in the Peripheral Olfactory Organs of the American Cockroach, Periplaneta americana

Abstract: Olfactory sensitivity exhibits daily fluctuations. Several studies have suggested that the olfactory system in insects is modulated by both biogenic amines and neuropeptides. However, molecular and neural mechanisms underlying olfactory modulation in the periphery remain unclear since neuronal circuits regulating olfactory sensitivity have not been identified. Here, we investigated the structure and function of these signaling pathways in the peripheral olfactory system of the American cockroach, Periplaneta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…This finding suggests that kinin analogs interact with G protein-coupled receptors expressed within gustatory sensilla similar to the way that peripheral olfactory neurons are modulated by tachykinin (16,17) and neuropeptide F (18)(19)(20). These peptides bind to GPCRs in olfactory receptor neurons (ORNs) or in circuits that modulate chemosensory signal-dependent feeding behaviors and food search (21).…”
Section: Discussionmentioning
confidence: 96%
“…This finding suggests that kinin analogs interact with G protein-coupled receptors expressed within gustatory sensilla similar to the way that peripheral olfactory neurons are modulated by tachykinin (16,17) and neuropeptide F (18)(19)(20). These peptides bind to GPCRs in olfactory receptor neurons (ORNs) or in circuits that modulate chemosensory signal-dependent feeding behaviors and food search (21).…”
Section: Discussionmentioning
confidence: 96%
“…Besides their myotropic activity, they also regulate aggression [114,115], act as modulators of olfactory perception and locomotion [116,117], and inhibit insulin signaling in the brain [118]. Tachykinins are expressed in the CNS and endocrine cells of the midgut [114,119,120].…”
Section: Tachykininmentioning
confidence: 99%
“…The presence of neurosecretory cells in insect antennae has only been previuosly described for mosquitoes 34 , but no other study has reported neuropeptide synthesis in these organs. The existence of similar cells could be the basis for the detection of a broad set of neuropeptide transcripts in the antennae of kissing-bugs (a total of 36 neuropeptides seems to be expressed) and other insects 23,35,36 . The expression of neuropeptide processing enzyme genes in the antennae was also detected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, variations in gene expression depending on nutritional status or development have been described for olfactory correceptors in the antennae of R. prolixus 10 . Nevertheless, information about elements regulating sensory gene transcription and the abundance of the corresponding proteins in insect peripheral organs is very limited [22][23][24][25] . Physiological mechanisms modulating peripheral responses to sensory stimuli involve signaling controlled by biogenic amines, hormones, and neuropeptides, as well as their target Gprotein coupled receptors (GPCRs) and nuclear receptors, overall controlling the functional status of sensory processes 16 .…”
Section: Introductionmentioning
confidence: 99%